LIFE QUALITY AND HEALTH IN THE WORKPLACE – CALL CENTER (Fiep Bulletin - online, 2016)
Even more companies adopt the services of call centers due the facility and operability of these professionals. This way, this article has as main objective to evaluate the satisfaction rate of the Call Center operators of a cement industry. For this evaluation, it was applied a questionnaire based in the eight pillars of Walton to 50 workers. The results showed that, despite the exhaustive workday, the collaborators consider the time interval enough to perform their activities and are proud to work in the organization. However, in the aspect “salary” most of the employees are dissatisfied, and this should be a matter that the company has to be attentive to avoid demotivation of the employees. This way, is conclusive that hardly is possible to obtain 100% of the employees satisfied, nevertheless, the organization should always attack their weakness, and create ways to humanize more the rank of staff, for example, giving recovery pauses and activities as labor gymnastics for the workers during their workday.
Keywords: Life Quality in the Workplace (LQW); Walton Model; Health; Labor Gymnastics.